Phosphate enema toxicosis in a pygmy goat wether - Hickman, Shirani A. (Canadian Veterinary Medical Association, 2004)
Phosphate enema toxicity was diagnosed in a 7-month-old, castrated male, pygmy goat. On presentation, clinical findings included mild depression, tachycardia, tachypnea, rumen stasis, muscle tremors, hypocalcemia, hypokalemia, hypochloremia, hyperphosphatemia, azotemia, and metabolic acidosis. Fluid diuresis and parenteral antimicrobial therapy resulted in recovery after 3 d of treatment.